40Ar/39Ar geochronology and geochemistry of the volcanic rocks from the Arivechi region, Eastern Sonora, Mexico. (July 2018) - Rodríguez-Castañeda, José Luis; Ortega-Rivera, Amabel; Velasco-Tapia, Fernando; Roldán-Quintana, Jaime; Lee, James K.W.
Abstract: This work provides new 40 Ar/ 39 Ar geochronological and geochemical data for the volcanism outcropping in the Arivechi region, Eastern Sonora, Mexico. Trachyandesite, dacite and rhyolite interbedded volcano-sedimentary rocks and dykes in the El Potrero Grande Unit have been dated between 76.7 and 61.1 Ma of age. The origin of the majority of these volcanic rocks could be explained by restricted assimilation of the ancient North American crust by mantle-derived magmas coupled with fractional crystallization in a subduction tectonic setting. Cretaceous-Paleocene volcanism was covered later by an ignimbrite deposit dated between 35.8 and 34.8 Ma of age. This volcanism could have been produced in a continental arc setting by crustal melting at depth of the upper-lower crust interface during the transition from a compressive to an extensional environment.